HUBUNGAN PAPARAN INFORMASI DAN PENGETAHUAN DENGAN KEBIASAAN MEMBACA LABEL INFORMASI GIZI PADA SISWA DI SMAN 14 SURABAYA - Imansari, Megawati Ayu; Dini, Cleonara Yanuar (STIKes Mitra Keluarga, 2023)
Introduction : Nutritional information labels are label that contained the nutritional information on food packaging.This study aims to analyze the relationship between information exposure and knowledge of the habit of reading nutritional information labels in SMA Negeri 14 Surabaya. students Method: It was a quantitative study with a cross-sectional design. The population in this study amounted to 636 students in grades 10 and 11. The sample was 116 students obtained by stratified proportioned sampling method. Result: The results showed that 75% of respondents didn’t read nutrition labels. The results of the analysis Chi-square showed there was a relationship between information exposure and the habit of reading nutritional information labels (p=0.005). Meanwhile, there was no relationship between knowledge and the habit of reading nutrition information labels (p=0.503). Conclusion: This study concluded that information exposure was related to the reading habit, while knowledge was not related